BENTUK PENYAJIAN TARI SAPUTANGAN DALAM BEDINDANG PADA ACARA BIMBANG ADAT DI KOTA MANNA KABUPATEN BENGKULU SELATAN - Riska Fitriani; Darmawati Darmawati; Herlinda Mansyur (FBS Universitas Negeri Padang, 2014)
ABSTRACT This article aimed at figuring out and describing the performance form of the Saputangan dance in Bedindang at the ceremony of Bimbang Adat at Kota Manna Kabupaten Bengkulu Selatan. The design of the research was descriptive qualitative research. The object of the research was the Saputangan dance in Bedindang at the ceremony of Bimbang Adat at Kota Manna Kabupaten Bengkulu Selatan. Data were obtained from the library study, observation, interview, and documentation. From the data analysis, it was found that the function of the Saputangan dance in the ceremony was as an entertainment and the performance form of the dance was dramatic. The performance of the dance included the components of series of movements, the floor design, the dancer, the music, make up and costumes, properties, the time and the place of performance. Kata Kunci : Bentuk Penyajian, Tari Saputangan, Bedindang, Bimbang Adat, Kota Manna